Resonant Raman scattering from phonons in GaAs/(GaAs)m(AlAs) n quantum wire structures - Maciel, A; Freyland, J; Rota, L; Kiener, C; Ryan, J; Mart, U; Martin, D; Morier-Gemoud, F; Reinhart, F (1995)
Raman spectroscopy has been used to measure phonons in GaAs v-groove quantum wire structures containing (001) and (111) GaAs/AlAs superlattice barrier regions. Resonance enhancement permits the identification of modes in different regions of the structure, and the measured phonon frequencies provide structural information which shows clear evidence of GaAs migration during growth from (001) surfaces into the grooves. Confined and interface phonons with large in-(111) plane wavevectors are observed. © 1996 American Institute of Physics.